Pendampingan Literasi Keuangan UMKM Di Ciledug, Tangerang Selatan - Audia Syifa Octaviani; Fauzan Ar Rizqy Haq; Ahmad Faris Kaisan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research uses a qualitative method with descriptive research type. With an estimated number of respondents SME 8 people. The data analysis techniques used are descriptive analysis and simple linear regression analysis. Based on the research results, Financial Literacy has an effect on Financial Management in SME members of SME entrepreneurs in South Tangerang. This needs to increase the knowledge of financial literacy for SME, in this study it is influenced by several things, namely the level of education, receipt of financial information, and the age of the SME actors.